Chapter Velimir Chlebnikov: dall'utopia neoslava a quella eurasiatica - IMPOSTI, Gabriella Elina (Biblioteca di Studi Slavistici, 2018)
This paper analyses Velimir Khlebnikov's early Pan-Slavic and anti-German ideological positions against the background of the Balkan crisis (1908, 1912) and the development of the Neo-Slavophile movement. Furthermore, we illustrate how Khlebnikov's encounter with Janko Lavrin influenced his linguististic conceptions, which in 1913 led to the publication of a series of articles in the newspaper "Slavyanin". Finally, we argue that some of these articles already showed a significant shift from his Neo-Slavophile ideas to a new conception, which turns towards the Eurasian continent as the arena for his utopian visions.